"Made in Canada": Local production networks in the Canadian fashion industry. (22nd December 2017) - Brydges, Taylor
Abstract : The fashion industry is a highly globalized industry increasingly dominated by international firms that favour flexible, efficient supply chains in order to produce trendy clothing at the lowest price. While much of the fashion industry follows the logics of global production networks, this paper presents a case where small, independent firms have chosen instead to engage with local production networks. Drawing on interviews with 87 independent fashion designers and key informants, this paper examines the following question: In the context of global production, why do independent fashion designers choose to work locally? In answering this question, three key findings are presented: the motivations of designers who emphasize timeless design and high‐quality local manufacturing; the strategies employed by designers to cultivate exclusivity and loyalty through the distribution of their collections; and the ways in which unique consumption experiences are utilized to articulate the values of their brand to consumers. While operating outside of the traditional fashion system provides independent fashion designers with the space for creativity, innovation, and control over their brand, it will be argued it also creates challenges with respect to growth beyond their niche market. Key Messages: Independent fashion designers in Canada demonstrate a commitment to local production networks in manufacturing, distribution, and consumption processes, resulting in the label of "Made in Canada" that is a defining aspect of their brands. Local production networks emphasize quality, local embeddedness, and creativity, which results in innovative independent fashion brands, but also creates challenges with respect to cost, growth, and scalability. Targeted investment is needed to strengthen the economic development potential of local production networks in the Canadian fashion industry.